A nationwide survey of combined central and peripheral demyelination in Japan. Issue 1 (11th February 2015) - Ogata, Hidenori; Matsuse, Dai; Yamasaki, Ryo; Kawamura, Nobutoshi; Matsushita, Takuya; Yonekawa, Tomomi; Hirotani, Makoto; Murai, Hiroyuki; Kira, Jun-ichi
Abstract : Objectives: To clarify the clinical features of combined central and peripheral demyelination (CCPD) via a nationwide survey. Methods: The following characteristics were used to define CCPD: T2 high-signal intensity lesions in the brain, optic nerves or spinal cord on MRI, or abnormalities on visual-evoked potentials; conduction delay, conduction block, temporal dispersion or F-wave abnormalities suggesting demyelinating neuropathy based on nerve conduction studies; exclusion of secondary demyelination. We conducted a nationwide survey in 2012, sending questionnaires to 1332 adult and paediatric neurology institutions in Japan. Results: We collated 40 CCPD cases, including 29 women. Age at onset was 31.7±14.1 years (mean±SD). Sensory disturbance (94.9%), motor weakness (92.5%) and gait disturbance (79.5%) were common. Although cerebrospinal fluid protein levels were increased in 82.5%, oligoclonal IgG bands and elevated IgG indices were detected in 7.4% and 18.5% of cases, respectively. Fifteen of 21 patients (71.4%) had abnormal visual-evoked potentials. Antineurofascin 155 antibodies were positive in 5/11 (45.5%). Corticosteroids, intravenous immunoglobulins and plasmapheresis resulted in an 83.3%, 66.7% and 87.5% improvement, respectively, whereas interferon-β was effective in only 10% of cases. CCPD cases with simultaneous onset of central nervous system (CNS) and peripheral nervous system (PNS) involvement exhibited greater disability, but less recurrence and more frequent extensive cerebral and spinal cord MRI lesions compared to those with temporarily separated onset, whereas optic nerve involvement was more common in the latter. Conclusions: CCPD shows different characteristics from classical demyelinating diseases, and distinctive features exist between cases with simultaneous and temporarily separated onset of CNS and PNS involvement.